2005
DOI: 10.1200/jco.2005.07.155
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large B-Cell Lymphoma: Clinical and Biological Characterization and Outcome According to the Nodal or Extranodal Primary Origin

Abstract: In the present series, the primary site of disease was associated with particular clinicopathologic features and outcome, though the latter largely depended on other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
199
10
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(238 citation statements)
references
References 39 publications
17
199
10
12
Order By: Relevance
“…Interestingly, Waldeyer ring involvement in this cohort was associated with improved survival, whereas extranodal involvement itself generally worsens survival. Lopez-Guillermo et al 13 also observed a positive prognostic impact of Waldeyer ring involvement on DLBCL before rituximab use. Consistent with our data, these patients were found to have significantly limited disease, better performance status, and fewer B symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, Waldeyer ring involvement in this cohort was associated with improved survival, whereas extranodal involvement itself generally worsens survival. Lopez-Guillermo et al 13 also observed a positive prognostic impact of Waldeyer ring involvement on DLBCL before rituximab use. Consistent with our data, these patients were found to have significantly limited disease, better performance status, and fewer B symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…When NHL has extranodal presence, the involved sites can be the gastrointestinal tract, bone, brain, testis, ovary, lung, nasopharynx, soft tissue, thyroid, kidney, liver, breast, skin, etc. [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphomas presenting in extranodal organs with no or only minor lymph node involvement were considered primary extranodal. 11 Immunohistochemistry Four-micrometer paraffin sections from formalinfixed material were dehydrated and deparaffinized according to standard procedures. Heat-induced antigen retrieval was then performed.…”
Section: Methodsmentioning
confidence: 99%